2001
DOI: 10.1055/s-2001-15031
|View full text |Cite
|
Sign up to set email alerts
|

Multiple paradoxe Embolien bei offenem Foramen ovale

Abstract: In patients with PFO, paradoxical embolism remains a challenging diagnosis that can be made highly probable by documentation of venous thromboses, pulmonary embolism, missing evidence of atherosclerosis in the vessels of the embolized organ and exclusion of other cardiovascular sources of emboli and prothrombotic coagulation disorders. Interventional closure of a patent foramen ovale appears to be the treatment of choice in proven paradoxical embolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Such diverse and relatively rarer presentations include acute limb ischaemia,4 6 7 renal infarction,8 9 ischaemia of the digestive tract10 and also myocardial infarction 11 12. Knobloch et al 13 reported a similar case in a young man with myocardial infarction, popliteal artery occlusion and carotid thrombus. The patient was then retrospectively found to have pulmonary embolism and PFO, which led to the diagnosis of paradoxical embolism.…”
Section: Discussionmentioning
confidence: 99%
“…Such diverse and relatively rarer presentations include acute limb ischaemia,4 6 7 renal infarction,8 9 ischaemia of the digestive tract10 and also myocardial infarction 11 12. Knobloch et al 13 reported a similar case in a young man with myocardial infarction, popliteal artery occlusion and carotid thrombus. The patient was then retrospectively found to have pulmonary embolism and PFO, which led to the diagnosis of paradoxical embolism.…”
Section: Discussionmentioning
confidence: 99%
“… Biographical information Diagnosis Treatment (Coronary; Pulmonary and PFO closure) 1 Collado Fareed Moses et al [ 3 ] 71 years female NSTEMI; PE; PFO C: Occlusion of RCA; Aspiration thrombectomy; Antiplatelet treatment not mentioned Pul: Not mentioned PFO closure: Not suitable due to severe pulmonary hypertension 2 Rovner et al [ 11 ] 70 years female STEMI (anterolateral wall); PE; PFO C: No acute occlusion; Lucent area in OM; Antiplatelet treatment not mentioned Pul: Oral anticoagulant (Warfarin) PFO closure: Deferred due to sepsis from a urinary tract infection; Later lost to follow-up 3 Hline et al [ 12 ] 86 years female STEMI (inferior wall); PE; PFO C: Occlusion of RCA. Aspiration thrombectomy; Intracoronary heparin and abciximab; Antiplatelet treatment not mentioned Pul: Lifelong anticoagulant (Warfarin) PFO closure: Multidisciplinary discussion not recommend 4 Smith et al [ 10 ] 69 years female STEMI (inferior wall); PE; PFO; Acute RV Failure C: Occlusion of PD and PL; Aspiration thrombectomy and balloon dilation; Oral aspirin Pul: Pulmonary angiography, interventional clot fragment and aspiration; and intra-arterial thrombolysis; Long-term anticoagulant (Warfarin) PFO closure: No 5 Knobloch et al [ 13 ] 38 years male STEMI (inferior wall); PE and DVT. Embolic occlusion of the left popliteal artery and left carotid artery; PFO C: Normal coronary angiogram Pul: Not mentioned PFO closure: Yes, transcatheter Others: Left popliteal: Embolus removal with Fogarty catheter; Left carotid embolus: surgery 6 Haghi et al [ 14 ] 61 years female NSTEMI; PE; PFO C: Balloon angioplasty (OM) and oral Aspirin Pul: Long-term anticoagulant (Warfarin) PFO closure: No …”
Section: Discussionmentioning
confidence: 99%
“…Besides, anticoagulation is associated with a high rate of long‐term side effects 12 . Transcatheter closure has yielded good results and little morbidity in some studies, 13–15 but is not a routine procedure for the combination of PFO and ASA, and can not be advised for all patients 16–18 …”
mentioning
confidence: 99%